Nutrition Disc as Media for Increasing Skills of Integrated Health Post Cadres at Jaten II Community Health Center, Karanganyar, Central Java, Indonesia - Annita Viesta Nirmala Dewi; Alya Ayu Kharisma; Agustina Hidayatul Khasanah; Alvina Dewi Maharani; Aninditya Choirun Annisa; Chusna Habiba; Dara Dinanti; Gading Nasywaa Aji Azzahra; Nita Diah Putri Andayani; Rachma Nadza Alfia Husna; Revi Gama Hatta Novika (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Stunting is the main nutritional problem faced by children in Indonesia. Nutrition discs can be used as one of the first steps to detect children with stunting. This study aimed to find whether nutrition discs are an effective medium for improving the measurement skills of health cadres to detect stunting early. Subjects and Method: This was a quasi-experimental study conducted in the Jaten II Community Health Center, Karanganyar, Central Java, from September 2022 to February 2023. A sample of 33 health cadres was selected using total sampling. The dependent variable was cadre skills. The independent variable was nutritional disc media. The instrument in this study used a questionnaire sheet containing 10 numbers regarding stunting knowledge and 25 numbers regarding anthropometric measurement skills. The data were examined using Wilcoxon sign rank test run on SPPS IBM 25. Results: The results of the univariate analysis showed that most of the respondents were aged 40-60 years (78.8%) with a high school educational background, 18 people (54.5%), 18 people (54.5%) had been cadres for 2-10 years and 24 people (72.7%) were not working. Bivariate analysis using the Wilcoxon sign rank test showed p=0.001 (OR=0.35; RR= 0.77 to 1.11; CI 95%). Conclusion: Nutrition discs are an effective medium for improving the measurement skills of health cadres to detect stunting early.